Early apixaban administration considering the size of infarction and functional outcome in acute ischemic stroke - Lee, Min Hwan; Koo, Jaseong; Kwon, Hanim; Chang, Jun Young; Kang, Dong-Wha; Kwon, Sun U.; Kim, Jong S.; Kim, Bum Joon (Frontiers in Neurology, 2024)
Background and purpose Atrial fibrillation-related stroke (AF-stroke) is associated with an adverse prognosis, characterized by a high incidence of progression, recurrence, and hemorrhagic transformation. Our study aims to investigate the potential benefits of stratified early administration of apixaban, taking into account infarct size during the acute phase, in order to enhance functional outcomes. Methods We conducted this study at a tertiary referral stroke center, enrolling acute AF-stroke patients who received apixaban during the acute phase. Infarct size was categorized as small, medium, or large based on diffusion-weighted imaging. Patients were divided into two groups: standard initiation (apixaban initiation based on guidelines, i.e., small: 4 days, medium: 7 days, large: 14 days after stroke) and early initiation (initiation before guideline recommendations) groups. We compared favorable outcomes (modified Rankin scale score ≤ 2) at 3 months post-stroke, stroke progression, early recurrence, and symptomatic hemorrhagic transformation (sHT) between the groups. Results Out of 299 AF-stroke patients, 170 (56.9%) were in the early initiation group. A favorable outcome was observed in 105 (61.8%) patients in the early initiation group and 62 (48.1%) patients in the standard initiation group (p = 0.019). Stroke progression or early recurrence occurred less frequently in the early initiation group (4.7% versus 13.2%, p = 0.007). Nevertheless, no difference in sHT was noted between the groups. Early initiation of apixaban was independently associated with favorable outcomes (odds ratio: 2.75, 95% confidence interval: 1.44–5.28, p = 0.002). Conclusion Our findings suggest that early initiation of apixaban, tailored to infarct size, could serve as a viable strategy to enhance functional outcomes. This approach may potentially decrease stroke progression and early recurrence without elevating the risk of sHT.